Malignant struma ovarii: From case to analysis. Issue 9 (4th July 2021) - Ayhan, Sevgi; Kilic, Fatih; Ersak, Burak; Aytekin, Okan; Akar, Serra; Turkmen, Osman; Akgul, Giray; Toyran, Atahan; Turan, Taner; Kimyon Comert, Gunsu
Abstract: Aim: To evaluate the clinico‐pathologic features, treatment options, prognostic factors, and survival outcomes of malignant struma ovarii based on a systematic literature review in association with our case study. Methods: A systematic review of the medical literature was performed to identify articles about malignant struma ovarii from January 1983 until July 2020. We evaluated 178 cases. Results: The 5‐year progression‐free survival (PFS) and overall survival (OS) of the entire cohort was 72.5% and 91%, respectively. In univariate analysis, younger age (<43 years), whole strumal cyst diameter > 95 mm, presence of a histologic type other than papillary classic‐type thyroid carcinoma within the tumor and lymphovascular space invasion were related to poor PFS. Patients who received radioactive iodine ablation (RIA) before the treatment failure had significantly higher PFS than those who did not receive RIA (94.9% vs. 64.8%, p = 0.041, respectively). In univariate analysis, PFS was significantly higher in patients who underwent gynecologic surgery followed by thyroidectomy and RIA compared with those who had surgical treatment only (94.5% vs. 64.3%, p = 0.05, respectively). However, this result could not be identified as an independent prognostic factor in multivariate analysis ( p = 0.207). Younger age and absence of capsular involvement were related to significantly increased OS. Histologic type was the only independent prognostic factor for PFS (hazard ratio: 3.30, 95% confidence interval: 1.122–9.748; p = 0.030) Conclusion: The most common histologic subtype was the papillary classic type. The presence of a histologic type other than the classic papillary thyroid carcinoma within the tumor was an independent adverse prognostic factor.